Developing an evaluation index system for the online learning literacy of physical education teachers in China - Tian, Hengxing; Sun, Mingzhu; Yin, Zhihua; Liu, Haohui; Li, Fangfei (Frontiers in Psychology, 2024)
Background The convenience of online learning helps physical education teachers overcome geographic barriers and promotes safe, accessible, high-quality education. This three-stage study developed an evaluation index system for online learning literacy of physical education (PE) teachers (OLLPET). Methods Using two rounds of the Delphi method and one round of the Expert ranking method, consult with 15 PE experts from universities, primary and secondary schools, and teaching-research staff to draw up, revise, and finalize an evaluation index system for OLLPET. Results Our OLLPET evaluation index system includes three first-level indicators, seven second-level indicators and 30 third-level indicators. The first-level indicators includes online learning values (OLV), online learning essential character (OLEC), and online learning key competencies (OLKC)–with equal weighting given to OLV (0.367) and OLKC (0.367) and slightly less given to OLEC (0.267). Conclusion The OLLPET evaluation index system is a theoretical yet practical tool that governments, schools, and teachers can use to evaluate PE teachers’ online learning literacy to improve their learning capacity in a targeted manner.